UPGRADING KESIAPAN BISNIS UMKM GULA SEMUT DI DESA SENDANG BARU LAMPUNG TENGAH MELALUI PELAKSANAAN PERIZINAN DAN SERTIFIKASI - Appin Purisky Redaputri; Hendri Dunan; Soewito Soewito; Okta Ainita; Lukmanul Hakim (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
The background of this community service program is utilizing raw materials, namely palm trees which grow a lot around forests in the Sendang Baru area, Central Lampung. This encourages the community to be able to earn more income to improve welfare, provides business opportunities for the community, fosters an entrepreneurial spirit for rural residents by managing businesses that are independent. This business opportunity must be in line with good business management arrangements. Not only utilizing existing commodities, but the business must also run well and the products produced are of high quality and have a clear market. One way to simultaneously improve product quality quickly and increase consumer confidence in this ant sugar product is to register a business license and product certification. Starting from the Business Identification Number (NIB), Food Safety Counseling (PKP) which can be used for the requirements for applying for Home Industry Registration (PIRT), as well as Halal certification. This activity involved the University of Bandar Lampung, PT PLN (Persero) UIP South Sumatra and KWT and the people of Sendang Baru themselves. In its implementation using a participatory method, the intention is to involve elements of society who are members of UMKM and Women Farmer Groups (KWT) in the village of Sendang Baru, but in reality it is attended by all village representatives in the district, Sendang Baru, this is a blessing from support from Kec. Sendang Agung.